DOMESTICATION AND FOREIGNIZATION AND THEIR IMPACTS TO TRANSLATION - Prasetyo, Johnny; Nugroho, Andy Bayu (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2013)
There are four problems in translating a text. The first and main problem is the language factor. The second problem is a social one, the third is the problem that has something to do with religion or belief, and the fourth one is the cultural problem. In short, the problems have a close relation to the language and culture. So, a translator should have a good mastery of the two languages, namely, the source language and the target one. This article discusses the problems of translation having to do with culture and its impacts to translation. The strategy of a translator to overcome the problems is determined by his/her ideology: domestication or foreignization.